HUBUNGAN SANITASI DAN PERSONAL HYGIENE DENGAN KEJADIAN DERMATITIS PADA MASYARAKAT DI WILAYAH KERJA PUSKESMAS GARUDA TAHUN 2024 - Soleha, Wilda Niatul; Purba, Christine Vita Gloria; Hayana, Hayana; Septiani, Winda; Wahyuni, Denai (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Dermatitis is a skin disease that affects the surface of the skin, caused by fungi, viruses, germs, and bacteria. This study aims to determine the relationship between sanitation and personal hygiene with the incidence of dermatitis in the community within the working area of Puskesmas Garuda. The study employed a quantitative method with a case-control design and consecutive sampling technique. The study population consisted of 531 cases and 35,518 controls, with a total sample of 128 respondents (64 cases and 64 controls). Data were analyzed using univariate and bivariate analysis with the Chi-Square test. The results showed a significant relationship between sanitation, personal hygiene, and the incidence of dermatitis, including clean water facilities (P-value = 0.001; OR = 3.462), waste disposal facilities (P-value = 0.0001; OR = 5.000), hand, foot, and nail hygiene (P-value = 0.0001; OR = 4.522), skin hygiene (P-value = 0.0001; OR = 4.041), and bed cleanliness (P-value = 0.0001; OR = 4.505). It is recommended that Puskesmas provides education to the community on the importance of maintaining personal and environmental hygiene to prevent disease. This includes the use of closed waste bins, sorting waste from the household level, and regular waste disposal. Hand, foot, and nail hygiene should also be maintained through regular handwashing, cleaning of feet, and trimming of nails. Routine assistance is necessary to create a clean home environment and support the implementation of clean and healthy living behaviors.Keywords: Sanitation, Personal Hygiene, Dermatitis